Pengaruh kepemimpinan kepala sekolah dan kompetensi guru terhadap kinerja guru di Sekolah Dasar Negeri Gugus 2 Kecamatan Tannjungsari - Sopia, Evip (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to analyze the influence of principal's leadership and teacher competence on teacher performance at Cluster II State Elementary Schools, Tanjungsasri District, Sumedang Regency. The research method uses a quantitative approach. The population is all Cluster II State Elementary Schools, Tanjungsari District, Sumedang Regency with 105 teachers. Data collection techniques using a questionnaire through the distribution of questionnaires. Analysis of research results using descriptive statistics, correlation and simple and multiple regression using SPSS. The results of the study prove that: 1) there is an influence of principal's leadership on teacher performance in Cluster II SDN throughout Tanjungsari District, Sumedang Regency. The magnitude of the influence of principal's leadership on teacher performance is 43.2%, the remaining 56.80% is determined by other variables; 2) there is an effect of teacher competence on teacher performance in Cluster II SDN in Tanjungsari District, Sumedang Regency, the magnitude of the influence of teacher competence on teacher performance is 52.10%, the remaining 47.90% is determined by other variables; and 3) there is an effect of principal leadership and teacher competence on teacher performance together of 75.9%, this means that principal leadership and teacher competence together can affect teacher performance in Cluster II throughout Tanjungsari District, District Sumedang is 75.9% and the remaining 24.10% is determined by other variables that are not examined.